Design of Optical Sensor Membrane Based on Polymer Poly(methyl methacrylate) for Paracetamol Detection in Traditional Herbal Medicine - Rimadani Pratiwi; Shelvy Elizabeth Suherman; Rajkannah A. L. Poongan; Mutakin Mutakin; Aliya Nur Hasanah (International Journal of Analytical Chemistry)
Generally, regulation states that herbal medicines are remedies containing plants or preparation of plants as active ingredients only. Paracetamol is one of the drugs that is frequently added in herbal medicine to enhance the effect as an analgesic. The government regulation disallows chemical drugs contained in herbal medicine due to the toxic effect of uncontrolled consumption. On this study, the optical sensor membrane from polymer poly(methyl methacrylate) (PMMA) was synthesized by phase inversion method and was used to detect paracetamol in herbal medicine. PMMA was made in three different concentrations 5%, 7.5%, and 10% and was mixed with ferric chloride (FeCl3), Folin-Ciocalteu, and Nessler reagent as specific colorimetric reagents for paracetamol detection, with a ratio of solvent:reagent was 6:4; 7:3; and 8:2. The result of the experiment shows that PMMA-FeCl3 7.5% (7:3), PMMA-Folin 5% (6:4), and PMMA-Nessler 5% (6:4) give the best performance for paracetamol detection. Real herbal medicine samples were analyzed to confirm the practical application of this sensor, and the result shows good agreement with UV-Vis data. The results show that optical sensor membrane which has been developed can be used as new detection method of paracetamol for community application.